2018
DOI: 10.1016/j.arth.2017.11.049
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Comparison of a Medial Pivot and Posterior-Stabilized Total Knee Arthroplasty With Respect to Patient-Reported and Radiographic Outcomes

Abstract: We found that patients who underwent the MP-TKA scored better on the FJS than those who underwent the PS-TKA; particularly with regard to deep knee flexion and stability of the prosthesis. The MP-TKA design may offer improved patient outcomes because of its highly congruent medial tibiofemoral articulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 38 publications
8
82
3
Order By: Relevance
“…16 Samy et al compared 76 MP articulations with 88 PS articulations in a retrospective review and found that although range of motion was not statistically different between the two groups, the MP group did statistically and significantly better in terms of the Forgotten Joint Score compared with the PS group, especially when looking at deep knee flexion and stability of the prosthesis. 17 A lateral pivot design has also been evaluated, which uses a higher level of lateral congruence to provide AP translational control and axial rotation and yet allows femoral rollback in deep flexion through asymmetry of the femoral component. This has been shown by Harman et al in a mixed cohort of PCL-retaining or resected knee arthroplasties to provide good-to-excellent outcomes in 84% of patients at 8 to 10 years of follow-up.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…16 Samy et al compared 76 MP articulations with 88 PS articulations in a retrospective review and found that although range of motion was not statistically different between the two groups, the MP group did statistically and significantly better in terms of the Forgotten Joint Score compared with the PS group, especially when looking at deep knee flexion and stability of the prosthesis. 17 A lateral pivot design has also been evaluated, which uses a higher level of lateral congruence to provide AP translational control and axial rotation and yet allows femoral rollback in deep flexion through asymmetry of the femoral component. This has been shown by Harman et al in a mixed cohort of PCL-retaining or resected knee arthroplasties to provide good-to-excellent outcomes in 84% of patients at 8 to 10 years of follow-up.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Based on these theoretical advantages, the design features of the medial pivot prosthesis may decrease the risk of patellofemoral joint problems [11,12]. Several studies have reported clinical satisfaction and survival analysis of TKA for this prosthesis [13][14][15][16], however, the comparison of clinical and radiographic results of this prosthetic patellofemoral joint with another prosthesis was rare [11].…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated the MS TKA to have significantly superior PROMs on all validated scales (FJS, KOOS, Western Ontario and McMaster Universities Osteoarthritis Index, and Oxford Knee Score), with the greatest difference on the FJS. Samy et al [8] found similar results with the FJS, with the MS TKA favored over a PS TKA. This was particularly true when patients were asked if they were aware of their knee when standing from a low-sitting position; an activity that requires mid-flexion stability [8].…”
Section: Discussionmentioning
confidence: 60%
“…Samy et al [8] found similar results with the FJS, with the MS TKA favored over a PS TKA. This was particularly true when patients were asked if they were aware of their knee when standing from a low-sitting position; an activity that requires mid-flexion stability [8]. No significant difference was seen between the MS TKA and the non-MS TKA groups according to VAS patient satisfaction, likely due to the well-recognized ceiling effect of VAS [17].…”
Section: Discussionmentioning
confidence: 60%